Gan-based Materials And Devices : Growth, Fabrication, Characterization And Performance. - Shur, Michael (Selected topics in electronics and systems ;, 2004)
The unique materials properties of GaN-based semiconductors havestimulated a great deal of interest in research and developmentregarding nitride materials growth and optoelectronic andnitride-based electronic devices. High electron mobility andsaturation velocity, high sheet carrier concentration atheterojunction interfaces, high breakdown field, and low thermalimpedance of GaN-based films grown over SiC or bulk AlN substratesmake nitride-based electronic devices very promising.